A Semantic Study of Renda’s Dialect (INDONESIA) - Nurfitri Ayu Cahyani; Waliyudin, Waliyudin (JURNAL PENDIDIKAN BAHASA, 2021)
This study aims to know are: (1) types of meaning in semantic that create in daily conversation used by Renda’s society (2) the dominant types of meaning in semantic that create in daily conversation used by different level of Renda’s society. There are sources of data are primary data and secondary data, primary data by taken videos conversation of Renda’s society, there are 3 videos conversation; children, academician and common society. Secondary data is taken from many semantic books. The result of this study showed that there are 37 extracts among 3 videos conversation of Renda’s society, the researcher found 6 Conceptual meaning, 6 Connotative meaning, 5 Social meaning, 3 Affective meaning, 9 Reflected meaning, 4 Collocative meaning and 5 Thematic meaning. Based on that result of types of meaning were create, the researcher concluded that reflected meaning was the dominant type of meaning in semantic that create in daily conversation used by Renda’s society.